A Fair Share of Work: Is Fairness of Task Distribution a Mediator Between Transformational Leadership and Follower Emotional Exhaustion? - Scheel, Tabea E.; Otto, Kathleen; Vahle-Hinz, Tim; Holstad, Torsten; Rigotti, Thomas (Frontiers in Psychology, 2019)
Drawing on social resource theory and the norm of equity, this research proposes fairness of task distribution as a mediating mechanism of the well-established relationship between transformational leadership and followers’ well-being, conceptualizing the latter as low emotional exhaustion. Using data from 479 German employees in a three-wave longitudinal study, we found transformational leadership to be related to fair task distribution over time. The perceived fairness of task distribution mediated the relationship between transformational leadership and follower emotional exhaustion (structural equation modeling) when excluding stabilities. Our results also show a reverse causation effect for emotional exhaustion and transformational leadership over a longer time period (within 20 months), suggesting a circular process, as well as a mediation by fairness of task distribution when excluding stabilities. The findings emphasize the importance of fair task distribution by leaders for followers’ well-being.